Research Report to the NIMH on the Sociological Perspective - Gronfein, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
You have just taken a job at the Neifnorg Research Corporation which is a social science "think tank" based in Indianapolis. The Neifnorg Corporation consults with governmental agencies and interested private sector groups on questions of health and health care policy, with a particular emphasis on questions involving mental illness and health.